Interplay between greenspace interactions and sense of place in Seoul City - Kim, Lankyung; Li, Ching (Frontiers in Sustainable Cities, 2024)
The intricate connection between urban residents and their surrounding greenspaces highlights the multifaceted relationship shaping individuals’ sense of place within urban environment. This study explores the influential relationship between greenspace interactions (GI) and the resultant greenspace sense of place (GSP) while considering four types of greenspaces (GT) as moderators. Employing partial least square-structural equation modeling (PLS-SEM), data was gathered from 400 participants, encompassing different GT within Seoul City, South Korea, to investigate the nuanced associations among psychological, physical, social, and environmental dimensions of GI and their impacts on place attachment (PA), sense of community (SoC), and utilitarian sense of place (USoP) in the GSP framework. Findings confirm a significant relationship between GI and GSP, emphasizing the role of environmental consciousness as a predominant factor influencing individuals’ overall perception on urban nature. Notably, despite conceptual expectations, the study revealed no moderation effect of different GT on the GI-GSP relationship, underscoring the universal relevance of urban greenspaces in fostering residents’ GSP. The result emphasizes the intrinsic value of urban greenspaces in shaping the preference of urban residents regarding urban nature.